Evidence of mitochondrial alterations in primary cardiac stromal cells from arrhythmogenic cardiomyopathy hearts. (10th June 2022) - Philippe, R; Volani, C; Medici, A; Texler, B; Pagliaro, A; Stadiotti, I; Meraviglia, V; De Bortoli, M; Guarino, A; Blumer, M; Pompilio, G; Pramstaller, PP; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): This research was funded by the Department of Innovation, Research and University of the Autonomous Province of Bolzano-South Tyrol (Italy), and by the Joint Project Südtirol- FWF (Italy-Austria) for A.R., J.T., A.M., R.P.. Background: Arrhythmogenic cardiomyopathy (ACM) is a genetic disease associated with sudden cardiac death and fibro-fatty replacement of myocardium. Recently, it has been demonstrated that oxidized lipid contributes to cardiac adipogenesis and that ACM hearts are characterized by an increase in oxidative stress. Purpose: As mitochondria are an important source of reactive oxygen species (ROS) within mammalian cells, the present work aims to evaluate if increased oxidative stress observed in ACM hearts is associated with altered mitochondrial function. Methods: The oxidative stress marker 4HNE was investigated together with the cardiomyocyte marker cardiac Troponin T on paraffin embedded human ventricular samples and analyzed by confocal microscopy. Human primary cardiac stromal cells (CStCs), obtained from either right ventricle biopsies of ACM patients or healthy cadaveric tissue donor (CTR), were used as cellular model as they are known for their contribution to adipogenesis in the ACM pathology. CStCs were cultured either in basal medium or adipogenic medium (ADIPO) in presence or absence of 500 nM of the ROS scavenger MitoTEMPO. After 7 days of adipogenic differentiation, intracellular lipid droplets accumulation and mitochondrial superoxide levels were measured in CStCs by confocal microscopy using BODIPY 493/503 (0.5 µM) and MitoSOX Red (5 µM) dyes, respectively. The oxidative phosphorylation (OXPHOS) and fatty acid oxidation (FAO) were also evaluated in CStCs by high resolution respirometry. Results: 4HNE staining was increased in heart tissues from ACM patients compared to CTRs and particularly evident in non-cardiomyocyte cells. In agreement, a higher MitoSOX fluorescence intensity was found in ACM-CStCs compared to CTR-CStCs in ADIPO medium, confirming higher ROS presence in patient cells. The treatment with MitoTEMPO was efficient in reducing ROS abundance, strongly suggesting mitochondrial origin. Lipid accumulation in ACM-CStCs was also prevented by MitoTEMPO treatment. Preliminary evidence further indicates that mitochondrial respiratory capacity is increased in ACM-CStCs versus CTR-CStCs exposed to adipogenic medium for 7 days. However, transmission electron microscopy analysis and Western blot analysis of Mfn1/2, Opa1, Fis1 and Drp1 did not show an evident alteration neither in mitochondria ultrastructure nor in the expression of proteins regulating mitochondrial dynamics. Conclusions: Our data support an alteration of mitochondrial activity in CStCs from ACM patients, apparently not linked to a modified network or morphology of mitochondria but associated with a higher ROS production.